(untitled) (Biological Sciences - PJSIR, 2004)
Vertebral anomalies have been reported in Liza carinata, Valamugil cunnesius and Therapon jarbua from Korangi creek and L. carinata collected from backwaters of Sandspit. Detail examination of external morphology and X-rays of fishes showed kypholordosis and scoliosis in the vertebral column. It is presumed that these effects are results of pollutants in the coastal systems of Korangi creek and Sandspit backwaters where heavy pollutants and domestic sewage of the Karachi city is discharged untreated. This study suggests the need of effective management measures to save fisheries resources of the creeks and coastal waters.